Geohazard Risk Management on Geotourism, Case Study: Pindul Cave, Gunung Kidul - Yogyakarta (Proceedings of the International Conference of Geological Engineering Faculty, 2021)
The geodiversity of Indonesia as an archipelago country has contributed huge benefits tothe development of geotourism. One of them is featured as Pindul Cave geosite in Gunung KidulYogyakarta, which is already running as a well-known tourism site within the Gunung SewuGeopark. In order to create a sustainable geotourism, it is necessary to have a good hazard riskmanagement, especially regarding to geohazards. Since Pindul Cave has not prepared themanagement yet, this study aims to assess the variables in the geosite, this includes the likelihoodand consequences, that will provide a holistic risk management plan. The highest geohazard riskcomes from floods and landslides on the geosite. The assessment result mentioned that Pindul CaveGeosite is included in the High-Extreme category, which means that geosite needs immediaterepairing action and even requires a specific plan on the managerial level in terms of handling andemergency conditions. In dealing with such risks, it is necessary to have engineering, administrativecontrol, and procurement of personal protective equipment (PPE).
Keywords: Geotourism; sustainable; Pindul Cave; geohazard; risk management